Structural Biomimetics of Non-smooth Pits for Ceramic Extruders and Its Reducing Adhesion and Resistance - Shengrui YU; Ping JI; Zhemin DAI; Lei XU; Zhihuan LIU; Wei LI; Huiting WU (工程科学与技术)
A ceramic extruder is a key piece of equipment for ceramic plastic forming, which plays a critical role in extruding mud with high density, strong plasticity, and uniform composition. However, due to the resistance to adhesion between the extruded clay and the barrel’s internal contact surface, the extruded clay often exhibits non-uniform velocity distribution, delamination, cracking, and other defects that seriously affect the surface quality and forming performance. Inspired by the surface structure of the dung beetle’s body, which reduces viscosity and resistance, this study analyzes the movement status of mud in the ceramic extruder’s head and researches a bionic design with a non-smooth, pit-shaped structure. Using surface modification technology, a pit-shaped bionic structure is implemented on the inner wall of the ceramic extruder’s head, disrupting the original layered order of the mud and altering the state of the water film. Furthermore, a geometric model of the dung beetlex’s pit-shaped bionic structure is established for the extruder’s head. Building on this, the structure is further optimized using the numerical calculation methods of COMSOL multiphysical field and orthogonal experimental design. Subsequent extruding experiments verified the effectiveness of the proposed method. The results showed that the geometric factors affecting the comprehensive performance of the bionic machine head, in descending order of impact, are the arrangement of non-smooth bodies, the spacing between adjacent non-smooth bodies, and the cross-sectional radius of non-smooth bodies. Moreover, when the pits were uniformly distributed on the head’s surface of the ceramic extruder in a parallel arrangement, with a pit radius of 1.5 mm and a distance between the centers of two adjacent pits of 4.5 mm, the drag reduction rate ( $λ_{f} $ <alternatives> </alternatives>) for clay extrusion reached 21.83%, the variance of relative angular velocity ( $λ_{s}^2 $ <alternatives> </alternatives>) decreased by 3.44%, and the clay extrusion efficiency increased by 11.95%. The surface of the extruded clay was smooth and free from defects, demonstrating that the non-smooth, pit-shaped bionic structure not only ensures high efficiency in clay extrusion but also reduces the adhesion and resistance between the extruded clay and the ceramic extruder. The proposed method holds significant theoretical and engineering value for the high-quality and efficient extrusion of clay.